2009
DOI: 10.1108/17471110910964487
|View full text |Cite
|
Sign up to set email alerts
|

Exploring socially responsible behaviour of Indian consumers: an empirical investigation

Abstract: PurposeWith growing consumerism in the country, Indians need to behave in a socially responsible manner for its sustainable development. This study sets out to explore the extent of the relationship between the demography and socially responsible behaviour of Indian consumers.Design/methodology/approachA slightly modified SRCB scale developed by Antil and Bennet with 34 Likert‐type items along with a few demographic questions is introduced among two equal groups representing urban and rural consumers, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
36
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 36 publications
8
36
2
1
Order By: Relevance
“…The research results of Plaut demonstrated that those under 25 years old showed a higher propensity for non-motorized travel [25]. The study of Klineberg et al [26] and Singh [27] showed that younger age groups gave higher attention to ecological environmental problems and a higher implementation rate of pro-environmental behavior and had a social responsibility in consuming behavior with sustainable development. However, some studies have pointed out that older age groups may pay more attention to recycling and find it easier to implement sustainable consuming behavior [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The research results of Plaut demonstrated that those under 25 years old showed a higher propensity for non-motorized travel [25]. The study of Klineberg et al [26] and Singh [27] showed that younger age groups gave higher attention to ecological environmental problems and a higher implementation rate of pro-environmental behavior and had a social responsibility in consuming behavior with sustainable development. However, some studies have pointed out that older age groups may pay more attention to recycling and find it easier to implement sustainable consuming behavior [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Both Scheiner's investigation of German residents' travel modes from 1976 to 2002 [43] and Hjorthol's investigation of Norwegian residents' travel modes from 1992 to 2005 [44] showed that the influence of gender on travel mode chosen fell off rapidly, in other words, there was no significant difference between males and females in the area of travel mode choice. Some studies indicate that there was no significant correlation between education and green travel behavior; however, some studies found a negative correlation; for instance, Singh found that the implementation rates of socially responsible consumer behavior of those people with a higher education were lower [27], and Böhler et al pointed out that the group with a higher educational background were more inclined to choose motorized travel [31]. In addition, some studies demonstrate that there was no significant correlation between income and green travel behavior; however, some studies found a negative correlation; for instance, Samdahl and Robertson found that the environmental awareness of low income residents was noticeably higher than the social average level [45], and both Singh [27] and Wang [29] found that low income residents were more inclined to implement recycling consumption behavior and socially responsible consumer behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Singh, 2009). For the environmentally concerned consumer, reducing current consumption amounts is not the only option today, as green alternatives for many products are available.…”
Section: Concept Of Willing To Purchase Green Productsmentioning
confidence: 99%